Love Language and Its Senses on Belonging and Solidarity in Polrestabes Surabaya - Himawan, Agung; Purnama Putra, Andra; Yuriadi; Mustofa, Rully; Wan Prala, Hendri (Sekolah Tinggi Ilmu Kepolisian, 2025)
Internal solidarity and a strong sense of belonging are essential for the sustainability of an organization. A solid and cohesive team enables the effective execution of tasks and the achievement of organizational goals. The behavior of love language among leaders and members is expected to foster solidarity and a sense of belonging within the Indonesian National Police (Polri) organization. This research aims to fill the gap in previous studies by investigating the influence of love language on the sense of belonging and solidarity within an organization. The primary objective of this study is to describe the impact of love language demonstrated by leaders at the Surabaya City Police (Polrestabes Surabaya) and the Satpamobvit of Polrestabes Surabaya. This qualitative study employs a descriptive approach, with data collected through observations, interviews, documentation, and literature reviews. Data analysis is based on Gary Chapman's (1992 & 2015) theory of love languages. The findings indicate that the use of love language by the leaders at Polrestabes Surabaya and Satpamobvit Polrestabes Surabaya positively influences the sense of belonging and solidarity among the members of the organization. The leaders’ love language behaviors encompass the five love languages: words of affirmation, giving gifts, quality time, acts of service, and physical touch. These behaviors have been shown to enhance the solidarity and sense of belonging within the organization. This research has the potential to be expanded to a broader scale, such as the East Java Police Region (Polda Jawa Timur).